Health service utilisation attributable to methamphetamine use in Australia: Patterns, predictors and national impact. (12th March 2017) - McKetin, Rebecca; Degenhardt, Louisa; Shanahan, Marian; Baker, Amanda L.; Lee, Nicole K.; Lubman, Dan I.
Abstract: Aim and background. We estimated health service utilisation attributable to methamphetamine use, its national impact and examined other predictors of health service utilisation among dependent methamphetamine users.Method. Past year rates of health service utilisation (number of attendances for general hospitals, psychiatric hospitals, emergency departments, general practitioners, psychiatrists, counsellors or psychologists, and dentists) were estimated for three levels of methamphetamine use (no use, < weekly, ≥ weekly) using panel data from a longitudinal cohort of 484 dependent methamphetamine users from Sydney and Brisbane, Australia. Marginal rates for methamphetamine use were multiplied by 2013 prevalence estimates from the National Drug Strategy Household Survey. Covariates included other substance use, demographics, mental disorders and drug treatment.Findings. Health service use was high. More frequent methamphetamine use was associated with more frequent presentations to emergency departments (incidence rate ratios 1.3–2.1) and psychiatric hospitals (incidence rate ratios 5.3–8.3) and fewer presentations to general practitioners, dentists and counsellors. We estimate methamphetamine use accounted for between 28 400 and 80 900 additional psychiatric hospital admissions and 29 700 and 151 800 additional emergency department presentations in 2013. More frequent presentations to these services were also associated with alcohol and opioid use, comorbid mental health disorders, unemployment, unstable housing, attending drug treatment, low income and lower education.Conclusions. Frequent methamphetamine use has a significant impact on emergency medical and psychiatric services. Better provision of non‐acute health care services to address the multiple health and social needs of dependent methamphetamine users may reduce the burden on these acute care services. [McKetin R, Degenhardt L, Shanahan M, Baker AL, Lee NK, Lubman DI. Health service utilisation attributable to methamphetamine use in Australia: patterns, predictors and national impact. Drug Alcohol Rev 2017;00:000–000]